Digitalisasi Sistem Informasi Pusat Kesehatan Masyarakat Berbasis Web - Praptomo, Sidik; Ramanda, Febri; Hermanto, Hermanto (Prodi Teknologi Informasi Universitas Muhammadiyah Muara Bungo, 2025)
Kuamang Jaya Community Health Center still relies on handwritten documentation in processing data, which often leads to reports being lost or damaged. In general, community health centers face various challenges in recording and reporting. Based on interview results, several issues were identified regarding the documentation and reporting of activities, including the use of handwritten information systems and a disorganized and cramped reporting storage area. This system is based on the prototype method. Prototyping is a systematic development approach that involves rapidly and incrementally building a program, allowing users to evaluate it early and continuously. Field study data were collected directly by the researcher from the Kuamang Jaya Community Health Center, Pelepat Ilir Subdistrict. The researcher conducted interviews to obtain information about the processes involved, carried out observations to confirm and refine the materials, and gathered direct information relevant to the research. The purpose of the system analysis phase is to provide a foundation for developing or improving the existing system. The results of the analysis can be used to create or modify a more effective and efficient system. This study resulted in the development of an information system that facilitates services at Kuamang Jaya Health Center by improving information dissemination, digitizing data, and enabling patients to register online more easily